2018
DOI: 10.1186/s12889-018-5700-6
|View full text |Cite
|
Sign up to set email alerts
|

History of co-occurring disorders and current mental health status among homeless veterans

Abstract: BackgroundHomeless veterans are at high risk for co-occurring disorders (COD), defined as mental illnesses that include at least one alcohol or other drug use disorder and at least one non-drug related mental disorder. However, epidemiological studies examining the prevalence of COD and associated mental health status in this population are limited. The objectives of the study were: (1) to describe a history of diagnosed mental disorders among homeless veterans admitted to a transitional housing program, and (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…This patient population has special medical needs, is older, poorer, sicker (with more diseases than veterans nationally) and has a higher percentage of men than the general adult population [ 12 14 ]. The creation of the VR instruments has been previously documented [ 13 – 16 ] and shown to be valid for the VA population [ 13 , 17 27 ] as well as other general US populations [ 28 – 35 ]. The English-language VR instruments have become an integral part of registries [ 36 ] and studies of National U.S. health programs [ 18 , 37 , 38 ] including the evaluation of the Medicare Advantage Program by the Centers for Medicare and Medicaid Services (CMS).…”
Section: Introductionmentioning
confidence: 99%
“…This patient population has special medical needs, is older, poorer, sicker (with more diseases than veterans nationally) and has a higher percentage of men than the general adult population [ 12 14 ]. The creation of the VR instruments has been previously documented [ 13 – 16 ] and shown to be valid for the VA population [ 13 , 17 27 ] as well as other general US populations [ 28 – 35 ]. The English-language VR instruments have become an integral part of registries [ 36 ] and studies of National U.S. health programs [ 18 , 37 , 38 ] including the evaluation of the Medicare Advantage Program by the Centers for Medicare and Medicaid Services (CMS).…”
Section: Introductionmentioning
confidence: 99%
“…Four of the 18 quantitative descriptive studies met all of the criteria outlined in the MMAT (Bonin et al, 2017;Garey et al, 2016;Garey et al, 2019;Gentil et al, 2019). Three studies did not describe their sampling criteria well enough to determine if it was adequate to answer the research question (Coleman, 2017;Ding et al, 2018;Ito et al, 2014). The risk of nonresponse bias was high in two studies (Robinson, 2019;Sun et al, 2012).…”
Section: Quality Appraisalmentioning
confidence: 99%
“…Additional physical factors directly affecting QoL among PEH were pain (Ito et al, 2014) and sleep (Crisanti et al, 2017). Mental health diagnoses (Crisanti et al, 2017) and dual mental health and substance use disorder diagnoses were also found to be significantly related to decreased QoL (Ding et al, 2018;McGuire et al, 2011). Additionally, others examined the effects of substance use on QoL and reported that those who used illicit drugs (Magee et al, 2019;O'Brien et al, 2015) and alcohol (Stergiopoulos et al, 2014) had lower QoL than participants who did not report substance use.…”
mentioning
confidence: 99%
“…Veteran homelessness has received public and scholarly attention in recent decades (Applewhite 1997; Creech et al 2015; Ding, Slate, and Yang 2018; Perl 2015; Tsai, Doran, and Rosenheck 2013; Tsai et al 2016; Tsai, Mares, and Rosenheck 2012). Initially, the issue of homelessness among veterans became noticeable in the 1970s and 1980s (Perl 2015).…”
Section: Literature Reviewmentioning
confidence: 99%